Metagenomic Analysis of Antarctic Biocrusts Unveils a Rich Range of Cold-Shock Proteins - Ekaterina Pushkareva; Josef Elster; Burkhard Becker (Microorganisms, 2023)
Microorganisms inhabiting Antarctic biocrusts develop several strategies to survive extreme environmental conditions such as severe cold and drought. However, the knowledge about adaptations of biocrusts microorganisms are limited. Here, we applied metagenomic sequencing to study biocrusts from east Antarctica. Biocrusts were dominated by cyanobacteria, actinobacteria and proteobacteria. Furthermore, the results provided insights into the presence and abundance of cold shock proteins (Csp), cold shock domain A proteins (CsdA), and antifreeze proteins (AFP) in these extreme environments. The metagenomic analysis revealed a high number of CsdA across the samples. The majority of the Csp recorded in the studied biocrusts were Csp A, C, and E. In addition, CsdA, Csp, and AFP primarily originated from proteobacteria and actinobacteria.